Aqueous Flow Reactor and Vapour‐Assisted Synthesis of Aluminium Dicarboxylate Metal–Organic Frameworks with Tuneable Water Sorption Properties. Issue 47 (27th July 2020) - Stassin, Timothée; Waitschat, Steve; Heidenreich, Niclas; Reinsch, Helge; Pluschkell, Finn; Kravchenko, Dmitry; Marreiros, João; Stassen, Ivo; van Dinter, Jonas; Verbeke, Rhea; Dickmann, Marcel; Egger, Werner; et al.
Abstract: Energy‐efficient indoors temperature and humidity control can be realised by using the reversible adsorption and desorption of water in porous materials. Stable microporous aluminium‐based metal–organic frameworks (MOFs) present promising water sorption properties for this goal. The development of synthesis routes that make use of available and affordable building blocks and avoid the use of organic solvents is crucial to advance this field. In this work, two scalable synthesis routes under mild reaction conditions were developed for aluminium‐based MOFs: (1) in aqueous solutions using a continuous‐flow reactor and (2) through the vapour‐assisted conversion of solid precursors. Fumaric acid, its methylated analogue mesaconic acid, as well as mixtures of the two were used as linkers to obtain polymorph materials with tuneable water sorption properties. The synthesis conditions determine the crystal structure and either the MIL‐53 or MIL‐68 type structure with square‐grid or kagome‐grid topology, respectively, is formed. Fine‐tuning resulted in new MOF materials thus far inaccessible through conventional synthesis routes. Furthermore, by varying the linker ratio, the water sorption properties can be continuously adjusted while retaining the sigmoidal isotherm shape advantageous for heat transformation and room climatisation applications. Abstract : Going with the flow : A collection of microporous aluminium fumarate‐mesaconate metal–organic frameworks (MOFs) are prepared by using an aqueous flow reactor and vapour‐assisted synthesis. The materials have a variable and, for some, previously unreported crystal structure, and their tuneable water sorption properties depend on the preparation method and linker content.